STRESS, DEPRESSION AND ANXIETY LEVELS AMONG PARENTS OF “LEARNING FROM HOME” DURING COVID-19 PANDEMIC - Denny Anggoro Prakoso; Alya’ Laudza; Yusuf Oka Mahendra; Naufal Hanif; Fitria Nurul Hidayah (Berkala Kedokteran, 2022)
Abstract: One of the consequences of the Covid-19 pandemic is the adaptation process and changes in the education process. During the Covid-19 crisis, the Indonesian Ministry of Education and Culture implemented a policy to aid in preventing Covid-19 spread through regulations governing the implementation of "Learning from Home" education. The implementation of this program which has been going on for quite a long time can create additional life burdens that produce a psychological impact on parents such as stress, anxiety, and depression. The purpose of this study is to determine the prevalence of stress, depression, and anxiety in parents of children who are "Learning from Home" as a response of the Covid-19 epidemic. An online survey was conducted from August 2020 until September 2020 among parents who have a minimum of one child with the age of children or adolescents. The Google Form was used to create a structured self-reported e-questionnaire, and the link was shared through WhatsApp. Respondents completed a survey measuring socio-demographic variables and the DASS-42 (Depression, Anxiety, Stress Scale) to measure stress, depression, and anxiety, after giving informed consent. Researchers received 225 online responses. Microsoft Excel and SPSS 21 were used to perform a univariate analysis on the data collection. Stress, depression, and anxiety were found to be prevalent among parents of “Learning from Home” children in 43.56%, 13.78%, and 18.22%, respectively. This research showed that during the Covid-19 pandemic, a significant number of parents of "Learning from Home" children encountered stress, anxiety, and depression symptomsKeywords: Stress-depression-anxiety; Learning from home; Parents; Covid-19